The development of family participation program in anemia prevention in children aged 6 months to 1 year in a well child clinic at Nong Chik Hospital - Jindarat, Siriporn (Thai Journal of Nursing, 2023)
This research and development aimed to develop the family participation program in anemia prevention in children aged 6 months to 1 years in a well-child clinic at Nong Chick Hospital. The Pender’s Health Promotion Model, was used in this research conceptual framwork. The development design comprised 3 phases; phase 1 exploring family participation, phase 2 developing the family participation program, and phase 3 implementing the family participation program. A sample of 20 families with children aged 6 months to 1 year, was purposively selected. Data were collected using a questionnaire, and a knowledge test, and a semi-structured interview guideline. Data were analyzed using descriptive statistics and content analysis. The results revealed that the family participation program included three phases of family assessment, planning and implementation, and home-visit assessment. After the program implementation by 3 nurses in 10 families, it was founded that only one child (10%) had anemia. Ninety percent of care providers were mothers who were the decision-maker. Eighty percent of them had knowledge on iron-deficiency anemia, complementary food, and iron supplements at a good level. .